2015
DOI: 10.1371/journal.pone.0121962
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of Shell Morphometrics in the Freshwater Pulmonate Gastropod Physa

Abstract: The cosmopolitan freshwater pulmonate snail Physa acuta hybridizes readily with Physa carolinae in the laboratory, although their F1 progeny are sterile. The two species differ qualitatively in shell shape, the former bearing a more globose shell and the latter more fusiform. We performed a hybridization experiment, measuring a set of 14 traditional (linear) and landmark-based shell morphological variables on even-aged parents and their offspring from both hybrids and purebred control lines. Parent-offspring r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…The persistent effect of family on every measured traits indicated that both genetic variation and/or maternal effects occured. Furthermore, Dillon & Jacquemin (2015) [ 68 ] showed a high heritability of shell morphological traits in Physa . An intensive knowledge is available on maternal effects and transmission of various factors in ovocytes [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The persistent effect of family on every measured traits indicated that both genetic variation and/or maternal effects occured. Furthermore, Dillon & Jacquemin (2015) [ 68 ] showed a high heritability of shell morphological traits in Physa . An intensive knowledge is available on maternal effects and transmission of various factors in ovocytes [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Köhler and Glaubrecht (2006) study was further supported by molecular work, thus make distinction among species more concrete. Most of the previous studies on gastropod shell morphometrics used at least four to thirteen shell characteristics ( Dillon Jr. & Jacquemin 2015 ; Ismail & Elkarmi 2006 ; Köhler & Glaubrecht 2006 ; Chiu et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other delineation studies are a combination of shell morphometrics with reproductive morphology ( Köhler & Glaubrecht 2003 ), nervous system, radula, or alimentary system ( Köhler & Glaubrecht 2006 ). Dillon and Jacquemin (2015) categorised shell morphometrics into two groups, traditional morphometrics and geometric morphometrics. The current study is categorised under traditional morphometrics which is based on linear measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the freshwater basommatophoran pulmonate snail Physa acuta has found widespread use as a model organism for a variety of evolutionary studies (Figure 1). Populations of P. acuta in both field and laboratory settings have played important roles in studies of mating behavior (Janicke, Vellnow, Lamy, Chapuis, & David, 2014;Janicke, Vellnow, Sarda, & David, 2013;Wethington & Dillon, 1996), sex allocation (Janicke & Chapuis, 2016;Wethington & Dillon, 1993), inbreeding depression (Jarne, Perdieu, Pernot, Delay, & David, 2000;Noel et al, 2016), reproductive isolation (Dillon, Robinson, & Wethington, 2007), gene flow (Bousset, Henry, Sourrouille, & Jarne, 2004;Van Leeuwen et al, 2013), speciation (Dillon, Wethington, & Lydeard, 2011), and ecophenotypic plasticity (Auld & Relyea, 2011;Dillon & Jacquemin, 2015;Gustafson, Kensinger, Bolek, & Luttbeg, 2014).…”
Section: Dillon Jrmentioning
confidence: 99%